Phragmolites (Gastropoda) from the Late Ordovician of the Peruvian Altiplano. (March 2020) - Ebbestad, Jan Ove R.; Gutiérrez-Marco, Juan Carlos
Abstract: Phragmolites lissoni new species is described from 11 specimens found in the Sandbian Calapuja Formation near Calapuja in Peru. The deposits are part of the Central Andean Basin. This is the hitherto only systematically described Ordovician gastropod from Peru. The species is from a brachiopod-dominated siliciclastic sequence and is associated with bryozoans. Most specimens are preserved as external molds, but latex casts yield excellent details of shell ornamentation and are used as a basis for evaluating this feature in the genus. The characteristic ornamentation of Phragmolites should be called corrugated lamellae, and the individual elements on these should be referred to as flutes. A descriptive terminology for these is suggested. The development and shape of the corrugated lamellae and flutes could be biomechanical process. A second component in lamellar formation is the alternation between regular incremental growth and formation of a lamella. Phragmolites is mainly found in shallow-water carbonate facies from tropical latitudes in the Sandbian and a mid-latitude presence in Peru is unexpected. Brachiopods from the same section in Calapuja show affinities with faunas of the Mediterranean margin of Gondwana but also weak links with Avalonia. Phragmolites is found abundantly in deeper-water facies in Laurentia, and a broad tolerance to facies and temperature and possible planktotrophy might have allowed a wide geographical dispersal of the genus. The scant record of Ordovician gastropods in the Central Andean Basin precludes comparison with the disparate record of the Ordovician gastropod taxa from the Precordillera, which do not include Phragmolites. UUID: http://zoobank.org/References/fbd7a43e-a610-42fd-a31d-b1a16fa69c9b